The Influence of Profitability, Firm Size, Growth, Liquidity, Asset Tangibility, and Non-Debt Tax Shield on Capital Structure - Febritya Ayu Wahyuni; Farida Titik Kristanti (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
Capital structure describes the company's financial proportions sourced from long-term debt and own capital as a source of corporate financing. This study aims to determine how the influence of independent variables, namely profitability, company size, company growth, liquidity, tangibility of assets, and non-debt tax shield, on the dependent variable, namely capital structure in property and real estate sector companies listed on the Indonesia Stock Exchange from 2015 to 2022. The method used is a dynamic panel regression analysis model using the Generalized Method of Moments (GMM) estimator with Eviews 12 analysis software. The results state that company size, company growth, liquidity, and tangibility assets partially have a significant positive and negative effect on capital structure. In contrast, profitability and non-debt tax shields partially have no significant impact on capital structure.